Bindepinde [stout rope] theology and religio-political dialogue in Zimbabwe - Dube, Edmore (HTS teologiese studies, 2023)
The article is motivated by a growing interest to solve local problems by infusing indigenous knowledge systems. It discusses the strained interface between religious and political actors using a local brand of theology, termed bindepinde [stout rope] theology. This theology is based on a local fable told to children, on how a Hare abused Hippopotamus and Elephant using a tethering rope. The folk story is taken as a metaphor in which Hare represents the sly politician abusing the rope to control Hippopotamus and Elephant, representing religious actors. Though Zimbabwe has a special place in this research, the research has shown that politicians act as third forces the world over. Religious entities often act as fodder for the progress of political demagogues, whose egos are legitimised by competing religious ideologies. Many religious bodies inadvertently enable politicians, thinking that they are fulfilling their own mandates. The article proposes negotiated versions of liberation theology and synodality as possible ways of overcoming inadvertent scaffolding of bindepinde theology. It concludes that while it may be difficult to tame the politician, it may be worthwhile to minimise the damage by making him focus more on the common good.Contribution: This article contributes bindepinde brand of theology as an indigenous theory of knowledge in the area of religio-political dialogue. The bindepinde theology has proved applicable to various contexts globally, where it thrives on dualism. Its mitigation lies in Kairos theology.